Respostas morfofisiológicas de Miconia spp. em diferentes fitofisionomias da Estação Ecológica do Panga, Uberlândia, MG - Marques, Marília (2015)
Miconia Ruiz & Pav. is the genus of Melastomataceae with greater representation in the Panga Ecological Station, Uberlândia, MG, occurring in various vegetation types characteristic of the Cerrado biome. In view of this, this study sought differences in functional traits and photosynthetic responses of five species of the genus occurring in such a diversified environment. In the first chapter, the aim was to evaluate the phenotypic plasticity of five species of the genus Miconia (Miconia albicans (Sw.) Triana, M. chamissois Naudin, M. fallax DC., M. ibaguensis (Bonpl.) Triana and M. stenostachya DC.) occurring in vegetation types subject to different light intensities (cerrado stricto sensu, cerradão, palm swamp edge and middle and gallery forest edge). In the second chapter, the physiological responses of M. chamissois, M. ibaguensis and M. stenostachya occurring in palm swamp and in gallery forest edge were evaluated in the dry and rainy seasons. It was noted that, for all species, the architecture and leaf traits in addition to the photosynthetic characteristics differed between populations established in the different study sites. Specific leaf area and internode length were higher in populations located in environments with higher levels of shading. M. chamissois and M. stenostachya had better photosynthetic performance in the palm swamp relative to the gallery forest edge, independent of the seasons. Taking into consideration the fact that palm swamps and gallery forests are restricted to the Cerrado biome and are suffering a remarkable process of degradation, M. chamissois and M. stenostachya are at risk, since both perform better in environments with greater availability of water in the soil.